SISTEM ANGKUTAN MULTIMODA DALAM MENDUKUNG EFISIENSI BIAYA LOGISTIK DI INDONESIA - Wahyu Wibowo; Irwan Chairuddin (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2017)
The purpose of this study is to obtain information from businessmen about how far multimoda transportation system that is applied during this time can affect the efficiency of existing logistics costs and what constraints that affect the implementation of the multimoda freight transportation system. The role of multimoda transport is growing very fast in recent decades which are in line with the growth in demand for goods consumed by society and production machines. The movement of goods is keep on increasing that requires an efficient transportation and can be executed quickly, so a system is very needed thatis called multimoda. This system is believed to reduce logistics costs, knowing that the Indonesia logistical index is still below compared to other countries in Asean, that is 24% of the GNP. The research found out that the Multimoda Transportation System has a strong relation with the Logistics Cost Efficiency of r = 0.89 and the regression relationships form Y = -0809 + 1:12 X + e, X = MultimodaTransport System and Y = Logistics Efficiency Costs. The influence of Multimoda System on Logistics Costs in the opinion of the respondents is 80%, assuming other factors are not observed